2016
DOI: 10.1097/hjh.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness in inflammatory bowel disease

Abstract: cf-PWV is increased in both ulcerative colitis and Crohn's disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…We did not establish any difference in arterial stiffness parameters between IBD subgroups, which is consistent with the meta-analysis by Zanoli et al and pilot research on the pediatric IBD population [9,62]. Furthermore, there was no difference in CST and arterial stiffness between different groups according to the anti-TNF-α therapy in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We did not establish any difference in arterial stiffness parameters between IBD subgroups, which is consistent with the meta-analysis by Zanoli et al and pilot research on the pediatric IBD population [9,62]. Furthermore, there was no difference in CST and arterial stiffness between different groups according to the anti-TNF-α therapy in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Arterial stiffness is a well-established predictor of the cardiovascular mortality and morbidity [42]. Findings of increased arterial stiffness in IBD patients compared to healthy subjects are consistent with most previous studies [9,52]. A pioneer study in 2012 on IBD patients showed increased arterial stiffness in comparison to healthy subjects [53].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations